2016
DOI: 10.18006/2016.4(2).156.168
|View full text |Cite
|
Sign up to set email alerts
|

A way of reproductive manipulation and biology of Wolbachia pipientis

Abstract: KEYWORDS Wolbachia Endosymbiotic bacteriaIntegrated pest management (IPM) Coleoptera ABSTRACTThe endo-symbiotic relationship between microorganism and eukaryotes are very common and has been broadly investigated from all insect species. The genus Wolbachia are obligatory intracellular bacteria that induce evolutionary alterations and have been frequently reported in egg cytoplasm's of various invertebrates including insects, spiders, mites, scorpions, crustaceans and nematodes, which exert a profound impact on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In the recent few years, most of the research focus has increased regarding Wolbachia infection in weevils [65] and more than 40 weevil species are reported for Wolbachia infection, which is arguably a larger number than from any other insect group [37,66]. This is contrary to the assumption that closely related species should trade off Wolbachia strains repeatedly and thus are expected to be associated with similar strains.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the recent few years, most of the research focus has increased regarding Wolbachia infection in weevils [65] and more than 40 weevil species are reported for Wolbachia infection, which is arguably a larger number than from any other insect group [37,66]. This is contrary to the assumption that closely related species should trade off Wolbachia strains repeatedly and thus are expected to be associated with similar strains.…”
Section: Discussionmentioning
confidence: 95%
“…Phylogenetic studies have indicated that these infectious strains are divided into eight (A-H) discrete supergroups [35]. Nevertheless, more recent literature has documented some more supergroups designated as A-K super orders [36,37]. Among these taxonomic supergroups, A and B are most likely to be documented in arthropods [38], whereas filarial nematodes, springtails, spiders, and termites are infected by distinct Wolbachia clades (C-D, E, F, G, and H) [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The combined applications of microbial pathogens may enhance their pathogenicity, persistence and infection rate (Ali et al 2016). Moreover, the issue of insecticide resistance can also be minimized as they exhibit novel modes of actions, which is lacking in conventional chemical insecticides (Qayyum et al 2015 andBala et al 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Contrary to this assumption, our study insects may share the same host ( P. canariensis and C. nucifera ) but progressively occupy two different Wolbachia strains which are helpful to discriminate these two beetle species. Due to higher incidence rate of Wolbachia in weevils (Ali et al 2016, 2018b) and numerous other insects and arthropods (Werren et al 1995; Jeyaprakash and Hoy 2000; Hilgenboecker et al 2008; Ali et al 2018b), current strategy to discarnate insect species, particularly B. longissima and O. nipae is valuable for further quarantine and management strategies.…”
Section: Resultsmentioning
confidence: 99%